2021
DOI: 10.5385/nm.2021.28.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Characteristics of Mortality Associated with Congenital Anomalies in Korean Children under 5 Years of Age

Abstract: Purpose: Studies have been conducted on the prevalence and infant mortality rate of congenital anomalies; however, studies on child mortality are rare. Therefore, we evaluated the characteristics of deaths associated with congenital anomalies among children born in Korea who died within 5 years of age.Methods: Birth-to-death cohort linked data of children under the age of 5 years from 2010 to 2013, and statistical data on the cause of death by age from 1999 to 2019, both provided by the Korea National Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Congenital diaphragmatic hernia (CDH) is a rare form of congenital disease with a frequency of 1 in 2,000 to 5,000 births; however, CDH mortality is high [1][2][3][4][5] . Kim et al 6) reported that CDH is the most frequent cause of death among infants aged <1 year (1.31%) between 2010 and 2013. Death of CDH patients is not due to the absence of the diaphragm itself, but due to secondary conditions, including pulmonary hypoplasia and pulmonary hypertension caused by infiltration of abdominal organs into the thoracic cavity due to the absence of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) is a rare form of congenital disease with a frequency of 1 in 2,000 to 5,000 births; however, CDH mortality is high [1][2][3][4][5] . Kim et al 6) reported that CDH is the most frequent cause of death among infants aged <1 year (1.31%) between 2010 and 2013. Death of CDH patients is not due to the absence of the diaphragm itself, but due to secondary conditions, including pulmonary hypoplasia and pulmonary hypertension caused by infiltration of abdominal organs into the thoracic cavity due to the absence of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%